Hidden Genetic Variation in LCA9‐Associated Congenital Blindness Explained by 5′UTR Mutations and Copy‐Number Variations of NMNAT1. Issue 12 (1st October 2015) - Coppieters, Frauke; Todeschini, Anne Laure; Fujimaki, Takuro; Baert, Annelot; De Bruyne, Marieke; Van Cauwenbergh, Caroline; Verdin, Hannah; Bauwens, Miriam; Ongenaert, Maté; Kondo, Mineo; Meire, Françoise; Murakami, Akira; et al.
Abstract : Leber Congenital Amaurosis (LCA) is a severe autosomal recessive retinal dystrophy leading to congenital blindness. A recently identified LCA gene is NMNAT1 (LCA9). Although most mutations in blindness genes are coding variations, there is accumulating evidence for hidden non‐coding defects or structural variations (SVs). Our study uncovered, for the first time, hidden genetic variation in NMNAT1‐associated LCA and emphasized a shift from coding to non‐coding (e.g. 5'UTR) mutations and repeat‐mediated SVs in the molecular pathogenesis of heterogeneous recessive disorders such as hereditary blindness. ABSTRACT: Leber congenital amaurosis (LCA) is a severe autosomal‐recessive retinal dystrophy leading to congenital blindness. A recently identified LCA gene is NMNAT1, located in the LCA9 locus. Although most mutations in blindness genes are coding variations, there is accumulating evidence for hidden noncoding defects or structural variations (SVs). The starting point of this study was an LCA9‐associated consanguineous family in which no coding mutations were found in the LCA9 region. Exploring the untranslated regions of NMNAT1 revealed a novel homozygous 5′UTR variant, c.‐70A>T. Moreover, an adjacent 5′UTR variant, c.‐69C>T, was identified in a second consanguineous family displaying a similar phenotype. Both 5′UTR variants resulted in decreased NMNAT1 mRNA abundance in patients' lymphocytes, and caused decreased luciferase activity in human retinal pigment epithelial RPE‐1 cells. Second, we unraveled pseudohomozygosity of a coding NMNAT1 mutation in two unrelated LCA patients by the identification of two distinct heterozygous partial NMNAT1 deletions. Molecular characterization of the breakpoint junctions revealed a complex Alu ‐rich genomic architecture. Our study uncovered hidden genetic variation in NMNAT1 ‐associated LCA and emphasized a shift from coding to noncoding regulatory mutations and repeat‐mediated SVs in the molecular pathogenesis of heterogeneous recessive disorders such as hereditary blindness.